2016
DOI: 10.1364/oe.24.005773
|View full text |Cite
|
Sign up to set email alerts
|

Optomechanically induced sum sideband generation

Abstract: Sum sideband generation in a generic optomechanical system is discussed in the parameter configuration of optomechanically induced transparency. The nonlinear terms of the optomechanical dynamics are taken account and the features of the sum sideband generation are identified based on the analytical treatment. The nonlinear optomechanical interactions between cavity fields and the mechanical oscillation, which emerging as a new frontier in cavity optomechanics, are responsible for the generation of the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Here, we only consider sum sidebands, then the efficiency of the upper and lower sum sideband can be define as η + s = | − √ η c κa + s /ǫ 1 | and η − s = | − √ η c κa − s /ǫ 1 | respectively, which are the ratio between amplitudes of the sum sideband and the first probe field, and thus dimensionless. In the previous work [37], it is shown that the efficiencies of sum sideband generation exhibit peak structure for some specific values of δ 1 and δ 2 . The specific values of δ 1 (δ 2 ) corresponding to these peaks are called as the matching conditions.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Here, we only consider sum sidebands, then the efficiency of the upper and lower sum sideband can be define as η + s = | − √ η c κa + s /ǫ 1 | and η − s = | − √ η c κa − s /ǫ 1 | respectively, which are the ratio between amplitudes of the sum sideband and the first probe field, and thus dimensionless. In the previous work [37], it is shown that the efficiencies of sum sideband generation exhibit peak structure for some specific values of δ 1 and δ 2 . The specific values of δ 1 (δ 2 ) corresponding to these peaks are called as the matching conditions.…”
Section: Resultsmentioning
confidence: 91%
“…While such linearized dynamics can explain many phenomena arise in cavity optomechanics, the nonlinear terms −iGδxδa and −hGδa * δa must be taken into account for the discussion of sum sideband generation, which is out of the frequency space of linearized dynamics. To calculate the amplitudes of the sum sidebands, we assume that the fluctuation terms δa and δx have the following forms [10,37]:…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear features of optomechanical systems with multiple probe field driven have been discussed recently [23], and spectral signals at difference sideband has been demonstrated analytically which provides an effective way for light manipulation and precision measurement in a solid-state architecture [24]. In the present work, difference-sideband generation in an optomechanical system coupled to a charged object is analytically investigated and precision measurement of electrical * haoxiong1217@gmail.com charges by means of the signals at difference sideband is carefully examined.…”
mentioning
confidence: 94%
“…Although a lots of quantum optical effects have been observed in the past decades and within different physics systems, there is renewed interest in such time-dependent dynamic effects which may include solitons 1620 , creation of short pulses 2125 , and multiwave mixing processes in the ultraslow propagation regime 2628 , etc. 2931 . In particular, time-dependent coherent control of the optical response of certain media that exhibit electromagnetic induced transparency (EIT) 1315 has also triggered a flurry of interest mainly due to its potential applications in integrated optics and quantum information science.…”
Section: Introductionmentioning
confidence: 99%